Stress-strain state of I-beam due to fillet welding - Bela, Sabo (Journal of Production Engineering, 1985)
This article describes the stress-strain state of an I-beam as a result of fillet welding. It provides an overview of total plastic and elastic longitudinal welding deformations and longitudinal welding stresses. The welding deformations are measured at ten measuring points using mechanical strain gauges with the utilization of extracted measuring sections.